2019
DOI: 10.1017/s1751731118002951
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of phenotypic udder traits to improve resilience to mastitis in Texel ewes

Abstract: There are no estimates of the heritability of phenotypic udder traits in suckler sheep, which produce meat lambs, and whether these are associated with resilience to mastitis. Mastitis is a common disease which damages the mammary gland and reduces productivity. The aims of this study were to investigate the feasibility of collecting udder phenotypes, their heritability and their association with mastitis in suckler ewes. Udder and teat conformation, teat lesions, intramammary masses (IMM) and litter size were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In addition, Capote et al [34] indicated a greater importance on the balance between the horizontal and vertical diameters of udder compared with length parameters. Other authors [12,16,18,[32][33][34] have suggested that the predictive capacity of udder measurements have important practical implications for breeding programmes to increase resilience to mastitis in the population [35]. In addition, Milerski et al [36] reported that the linear scores for udder depth, cistern depth, teat position and teat size would permit prediction of future correlated responses in milk-oriented selection schemes in the Tsigai, Improved Walachian and Lacaune breeds.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Capote et al [34] indicated a greater importance on the balance between the horizontal and vertical diameters of udder compared with length parameters. Other authors [12,16,18,[32][33][34] have suggested that the predictive capacity of udder measurements have important practical implications for breeding programmes to increase resilience to mastitis in the population [35]. In addition, Milerski et al [36] reported that the linear scores for udder depth, cistern depth, teat position and teat size would permit prediction of future correlated responses in milk-oriented selection schemes in the Tsigai, Improved Walachian and Lacaune breeds.…”
Section: Discussionmentioning
confidence: 99%
“…The measurable parameter, UP, despite presenting significant differences between the different groups of SCC, did not show differences between the lowest cell count group, associated with healthy animals, and the group with the highest SCC, associated with bacterial infection. The significant differences found between SCC groups may be due to the influence of lactation stage and udder fullness [25], revealing that UP may not be a good indicator of udder inflammation.…”
Section: Relationships Between Udder Traits and Somatic Cellsmentioning
confidence: 89%
“…Indeed, supernumerary teat removal correlates with a reduced incidence of subclinical mastitis in Dutch dairy heifers, although this observation could point to wider management differences between farms implementing different removal policies, rather than necessarily reflecting a direct effect (Santman‐Berends et al ). In small ruminants, as in cattle, bacterial mastitis is a major health issue with welfare implications (Hughes & Watson, ), in both dairy sheep (Bramis et al ) and those used for meat production (Phythian et al ; Crump et al ; Phythian et al ). It has been suggested that poor udder conformation, including the presence of supernumerary teats, may also constitute a minor, but notable, risk factor for acquisition of new intramammary infections (Vasileiou et al ), potentially as an indirect effect due to impairment of lamb sucking and consequent inefficient removal of milk (Menzies & Ramanoon, ).…”
Section: Introductionmentioning
confidence: 99%